PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA QUESTION CARD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 190 BARRU - Eva Kurniati; Nur Fitria Ningsih; Nurul Aulya Putri; Sri Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this study is to investigate the application of the Teams Games Tournament (TGT) learning model combined with Question Card media to improve student learning outcomes in mathematics. The study was conducted at UPTD SDN 190 Barru, focusing on 15 fourth-grade students. Initial observations revealed that most students struggled with understanding mathematics, particularly in flat shapes, due to monotonous teaching methods and low student motivation. The TGT model, known for its cooperative nature and competitive elements, was implemented to enhance student engagement and motivation. Question Card media, which stimulates active learning through questions and visuals, was used to complement the TGT model. This Classroom Action Research (CAR) followed a four-stage process: planning, action, observation, and reflection. The results showed that after implementing the TGT model with Question Card media in the first cycle, 53.3% of students achieved the minimum completeness criteria (KKM), and after the second cycle, 86.7% of students achieved KKM. The study concludes that the combination of TGT and Question Card media significantly improves student learning outcomes in mathematics.